The Influence of Age Gap on Differentiated Arabic Language Learning in Heterogeneous Students at Sekolah Indonesia Makkah - Putri Hanan; Roojil Fadilah (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2026)
This study employed a quantitative approach with a correlational comparative design to analyze the relationship between students’ age and Arabic language learning outcomes and to identify factors influencing age differences in Arabic language learning at Sekolah Indonesia Makkah. From a total population of 77 students, a sample of 20 students was selected using purposive sampling based on specific research criteria, particularly students who had complete academic records and were enrolled in heterogeneous classes with noticeable age variation. Data were collected through report card documentation and questionnaires measuring learning readiness, motivation, learning environment, and parental support. Considering the relatively small sample size, non-parametric statistical techniques were applied to ensure the robustness of the analysis. Data were analyzed using the Spearman Rank correlation test, independent sample tests, and multiple linear regression with SPSS version 25. The findings indicate that student age has no significant relationship with Arabic learning outcomes (correlation value = 0.012; sig. = 0.959 > 0.05). Similarly, the independent sample test shows no significant differences in learning outcomes among different age groups (sig. = 0.791 > 0.05). These results suggest that age differences do not significantly influence students’ Arabic learning outcomes, indicating that age is not a primary factor determining students’ success in heterogeneous classes. Instead, learning motivation particularly intrinsic motivation plays a crucial role in encouraging students to achieve optimal learning outcomes. Therefore, efforts to improve students’ achievement should focus on strengthening intrinsic motivation.